The Effect of Domperindone on Intestinal Motility and Bacterial Overgrowth in Patients with Liver Cirrhosis - Yustar Mulyadi; Rino Alvani Gani; Murdani Abdullah; Hamzah Shatri (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTBackground: Spontaneous bacterial peritonitis (SBP) is a common serious complication of liver cirrhosis mainly caused by bacterial translocation (BT) into ascites fluid. The most essential issue that affects BT is small intestinal bacterial overgrowth (SIBO), which usually caused by gastrointestinal dysmotility. This study was aimed to evaluate the prokinetic effects of domperidone on gastrointestinal motility and small intestinal bacterial overgrowth and the correlation between restoration of motility and the incidence of SIBO in patients with liver cirrhosis.Method: A cross-over double blind clinical trial was conducted on patients who were treated at the ward and outpatient clinic from Division of Hepatology in Cipto Mangunkusumo Hospital, Jakarta and Soedarso Hospital, Pontianak between September 2010 and March 2011. All patients suffered from liver cirrhosis with ascites, gastrointestinal dysmotility and SIBO were included in the study. Out of 34 eligible patients, 16 patients received placebo and 18 patients received prokinetics (domperidone). Wilcoxon test was performed to analyze the comparison of SIBO before and after treatment in the placebo group; while paired T-test was employed for the prokinetics (domperidone) group. To evaluate improved balance of SIBO in the placebo and domperidone group, a Chi-square test was performed.Results: In the placebo group, 61.8% patients experienced SIBO; while in the prokinetics group, SIBO occurred only in 2.9% patients. Restored gastrointestinal motility took place in the prokinetics group with reduced median value for orocaecal transit time from 120 minutes into 90 minutes (p = 0.0001). In contrast, it went worse in the placebo group, i.e. from 90 minutes into 110 minutes (p = 0.002). There was a significant correlation between restored gastrointestinal motility and SIBO (p = 0.0001). Similarly, so does the effect of administering prokinetic agent on restored gastrointestinal motility (p = 0.0001) and SIBO (p = 0.0001).Conclusion: The administration of prokinetics has been proven effective to restore gastrointestinal motility that may lead to reduced incidence of SIBO in patients with liver cirrhosis. Keywords: prokinetics, breath hydrogen test, dysmotilitas, bacterial overgrowth